(untitled) (Plant Tissue Culture and Biotechnology, 2020)
An efficient method of plant regeneration and subsequent growth and development of Dendrobium hybrid Sonia was developed using intact seedling, shoot tip and thin cell layer. Maximum number of PLBs was obtained in MS liquid medium supplemented with 0.5 mg/l NAA and 1mg/l BAP through shoot tip and thin cell layer culture (TCL). Highest number of adventitious shoot formation was recorded in 0.5 mg/l of NAA and 2 mg/l of BAP through shoot tip culture. In shoot tip and TCL cultures, the necrosis was checked in presence of NAA (0.5 mg/l) and BAP (1 mg/l). Maximum callus frequency was recorded in NAA and BAP (0.5 mg/l) through thin cell layer culture. Direct PLB formation was better at 1.0 μM concentration in all the three polyamines tested. Three polyamines tested were effective in direct PLB formation as well as adventitious shoots. Plant Tissue Cult. & Biotech. 30(1): 77-86, 2020 (June)